SAT0648 Coxalgia in hemophilic patients. sonographic evaluation of a not target joint. (12th June 2018) - Melchiorre, D.; Castaman, G.; Linari, S.; Matucci-Cerinic, M.
Abstract : Background: Background : Spontaneous bleeding in haemophilia shows a predilection for joints, and repeated hemarthrosis induce synovial inflammation, cartilage degeneration and bone damage, leading to hemophilic arthropathy. The hip is not a target joint and its involvement is not easy to be distinguished from other conditions which may provoke pain referred to the hip. Objectives: Objectives: Aim of the study was to analyse the different sonographic findings related to different pain producing conditions. Methods: Methods: Thirty patients with haemophilia A and monolateral coxalgia were examined. Sonographic exam (US) was performed in all patients by Esaote equipment My Lab 70 with linear probe 4–13 MHz and power Doppler. The iliopsoas muscle and its bursa, the greater trochanteric bursa, and the hip joint were analysed. Sonographic findings in the joint were scored (score ranging from 0 to 21) for effusion, bone remodelling, cartilage damage, synovial hypertrophy, hemosiderin, osteophytes, hemarthrosis, erosion and fibrotic septa. The World Federation of Haemophilia (WFH) orthopaedic joint scale score and the radiologic Pettersson score were evaluated in all patients. Results: Results : US showed effusion in 20 hip joints (67%), bone remodelling in 18 (60%), cartilage damage in 10 (33%), synovial hypertrophy in 12 (40%), hemosiderin in 4 (13%), osteophytes in 7 (23%), hemarthrosis in 10 (33%) with power Doppler activity (>3 flags). In no patient erosion or fibrotic septa were observed. Fifteen out of 30 joints showed US score ≤5, and 15 US score >5. In 8 patients a hematoma of iliopsoas muscle was present, in two patients great trochanteric bursitis was detected. WFH mean score value was 39.5 (range 12–57) and the mean Pettersson score value was 10.4 (range 6–12). Conclusions: Conclusions : Surprisingly, in most cases (67%) coxalgia was not related to trochanteric bursitis or iliopsoas muscle involvement but was due to hemophilic arthropathy of the hip which is not a target joint. Moreover, power Doppler allowed to detect hemarthrosis in 33% of patients, supporting the hypothesis that vascular changes and remodelling in haemophilia are associated with bleeding and joint damage 1 . Reference: [1] Bhat V, et al. Vascular remodeling underlies rebleeding in hemophilic arthropathy. Am J Hematol2015;90:1027–1035. Disclosure of Interest: None declared